Pelatihan Pengoperasian Alat Berbasis Arduino Uno Dengan Sensor Ultrasonik Sebagai Detektor Dini Pasang Surut Air Laut Yang Berpotensi Tsunami Pada Mgmp Fisika Kota Ternate - Iqbal Limatahu; Chumidach Roini; Husnin Mubarok (Jurnal Ilmiah Wahana Pendidikan, 2022)
The city of Ternate is an area whose territory consists mostly of ocean, so the people need an understanding of accurate tools to detect sea water levels which have the potential to become tsunamis and sometimes accompanied by earthquakes. For example, the educational community, teachers who are members of the Ternate City Physics MGMP, need to be given socialization and training on how to operate Arduino Uno-based tools which can provide signals when exposed to high tides via their ultrasonic sensors. The method for implementing the Community Partnership Program begins with identifying problems in coastal communities and high school physics teachers, followed by socialization, demonstrations and training on how to operate Arduino Uno-based tools. The activity is known to have increased physics teachers' understanding of the existence and benefits of the Arduino Uno by 100% and skills in operating the tool by 89.1%. Activity participants rated this activity as very important with an average result of 97.4%; the accuracy of the activity method was 95.6%; instructor expertise in delivering material was 97.1%. All participants (100%) who took part in the activity stated that this skill was important in teaching physics at school.